Different growth responses to feed ration levels in two freshwater turtle juveniles, the Chinese three-keeled pond turtle Mauremys reevesii and the red-eared slider Trachemys scripta elegans - Changyi Zhang; Shufen Jiang; Xinyue Liu; Siting Zhong; Wenyi Zhang (Aquaculture Reports)
Turtle aquaculture is a rapidly expanding industry whereas the knowledge about the feed ration-dependent growth performances of turtles is limited. The present study investigated growth performance, physiological changes, and alterations in gut microbiota at gradient daily feed rations in two turtle juveniles, the Chinese three-keeled pond turtle Mauremys reevesii and the red-eared slider Trachemys scripta elegans. During 14 days of feeding, the feed rations exceeding 1 % body mass induced the rapid growth of both two turtles. The growth rates further increased at the feed ration of 2.5 % body mass in T. scripta elegans, but not in M. reevesii. Increased feed rations enhanced glucose metabolism in the liver of T. scripta elegans and the muscle of M. reevesii, respectively. Fatty acid metabolism was activated in both two turtles and protein metabolism was enhanced in M. reevesii. Accumulated triglyceride or protein was observed in the liver of T. scripta elegans and the muscle of M. reevesii. The regulation of succinate dehydrogenase and insulin-like growth factor 2 may relate to these processes. Raised feed rations changed redox homeostasis and decreased immune function in M. reevesii. High feed rations increased gut pathogens in M. reevesii whereas increased the probiotic Lactobacillus in the gut of T. scripta elegans. These interspecific differences may contribute to the different growth performances between these two turtle species under high food availability. Our results provide information for feed management and optimizing feeding efficiency in turtle aquaculture, and can guide the potential strategies to improve the growth performance of freshwater turtles.